Warm Season Grain Legume Landraces From the South of Europe for Germplasm Conservation and Genetic Improvement - De Ron, Antonio M.; Bebeli, Penelope J.; Negri, Valeria; Vaz Patto, Maria Carlota; Revilla, Pedro (Frontiers in Plant Science, 2018)
Currently, there is a high concern from consumers regarding food quality, with emphasis on the origin of food sources. We here review the current situation of beans (Phaseolus spp.) and cowpea (Vigna unguiculata (L.) Walp.) landraces in the South of Europe focusing on morpho-agronomic and genetic diversity and physiological adaptation to the different agrosystems, including the symbiotic association with rhizobia. Despite the reduction in the production and consumption of grain legumes in Southern Europe, the variability of common bean, runner bean and cowpea landraces in this region is adequately preserved ex situ in germplasm banks and in breeder collections in Portugal, Spain, Italy and Greece; however, on-farm (in situ) conservation in isolated areas mainly in gardens and small fields for farmers own consumption and local markets is not guaranteed. This variability can be used for the genetic improvement of varieties, which will result in environmental-friendly improved legumes for a sustainable production in the South of Europe as well as in other regions of the World.